Development and characterization of pullulan-polymethacrylate free films as potential material for enteric drug release - Isabela Angeli de Lima; Suelen Plaza Pomin; Osvaldo Albuquerque Cavalcanti (Universidade de São Paulo, 2017)
ABSTRACT Free films of pullulan-polymethacrylate associations were produced by casting process to develop a novel target-specific material. For characterization, tests of water vapor permeability, swelling index, infrared absorption spectroscopy, thermogravimetric analysis, scanning electron microscopy and mechanical analysis were performed. The polysaccharide concentration directly influenced vapor permeability and swelling, increasing the values of the latter up to five times when added in a proportion of 20% (per weight). The individual properties of each polymer were maintained, and chemical interactions were not detected. The films were found to be thermally stable and they had unaltered mechanical properties with the addition of the polysaccharide. The microscopic analysis revealed rugosity that was proportional to pullulan and disorganization of the polymer network at pH 6.8. These results suggest that this novel material has potential for enteric drug release because of synergism between pH and enzyme dependence.